(untitled) - Betz, Frederick (Englewood Cliffs, N.J., 1987)
Set as a prescribed text or additional reading in some Australian universities over the last decade, this book does not now meet the needs of lecturers or tutors or students in today's learning environment. Published in 1987 it has now been overtaken by better publications on this most fascinating of subjects.
Keywords: Technological innovations,Research, Industrial,Đổi mới công nghệ,Nghiên cứu, công nghiệp; Management,Management,Quản lý,Quản lý